Rhizoma peanut genotype and planting date affect biomass allocation patterns and establishment performance. Issue 3 (16th April 2020) - Aryal, Parmeshwor; Sollenberger, Lynn E.; Kohmann, Marta M.; da Silva, Liliane S.; Shepard, Erin M.; Cooley, Katie D.; Rowland, Diane L.; Dubeux, Jose C. B.
Abstract: Rhizoma peanut (RP, Arachis glabrata Benth.) is an important perennial forage legume, but its adoption can be limited by relatively slow establishment. Genotype and temperature after planting of rhizomes likely affect partitioning of stored and new photoassimilates, but their impact on establishment rate is not known. To assess these relationships, planting date and RP entry effects were measured on biomass partitioning and growth responses. Treatments were all combinations of two planting dates (spring and summer) and four entries ('Florigraze', 'UF Peace', 'UF Tito', and the germplasm Ecoturf) replicated four times, with new plots planted in each of 2 yr. Spring‐planted Florigraze outperformed UF Peace in shoot count, shoot biomass, and root‐rhizome biomass through much of the year of planting. When planted in summer, UF Tito and UF Peace generally had earlier and greater shoot emergence, lesser root‐rhizome/shoot ratio, taller canopy height, and lesser leaf/stem ratio than Ecoturf or Florigraze. Across years, shoot biomass in the year after planting was greater for UF Peace and UF Tito than for Ecoturf and Florigraze when planted in summer (490, 387, 265, and 157 g m −2, respectively) and greater for UF Peace than Ecoturf or Florigraze planted in spring (349, 243, and 201 g m −2, respectively). UF Tito and UF Peace had greater shoot biomass in the year after planting for summer than for spring plantings, but there was no season effect for Ecoturf and Florigraze. Summer planting favored rapid establishment of upright cultivars UF Tito and UF Peace, but Ecoturf and Florigraze were less affected by season.